Fundamental managerial accounting concepts - Edmonds, Thomas P. (McGraw-Hill/ Irwin, 2008)
Fundamental Managerial Accounting Concepts 4e is organized in a distinctive way, particularly in the first six chapters. The objective is to establish a coherent, integrative framework that enables students to build knowledge in stepwise fashion. The authors’ goal is for students to understand the underlying principles of accounting, not just memorize content.